Developing Shared Leadership through Encounter Group Training - Taneja, Anshul (Journal of Commerce and Trade, 2009)
One milestone in the development of leadership theories is that of shared leadership. This concept brings about the function of leadership being shared amongst team members through the collective development of vision, shared responsibility, shared work goals, trust and free flow of information. The key to the success of shared leadership lies in open communication. Encounter group training is a powerful tool to open up team members and bring about the free communication and trust that will allow interpersonal sharing. This training methodology can play a significant role in shared leadership by developing the very qualities necessary for it to happen. The article is divided into five sections. After the introduction, a section is devoted to the concept of shared leadership followed by a section on encounter groups. The next section elaborates on the working of encounter groups followed by a case study of an encounter group session conducted by the author. The last section contains the concluding observations.